Diagnostics of pediatric supratentorial RELA ependymomas: integration of information from histopathology, genetics, DNA methylation and imaging. (28th November 2018) - Pagès, Mélanie; Pajtler, Kristian W.; Puget, Stéphanie; Castel, David; Boddaert, Nathalie; Tauziède‐Espariat, Arnault; Picot, Stéphanie; Debily, Marie‐Anne; Kool, Marcel; Capper, David; Sainte‐Rose, Christian; Chrétien, Fabrice; et al.
Abstract: Ependymoma with RELA fusion has been defined as a novel entity of the revised World Health Organization 2016 classification of tumors of the central nervous system (CNS), characterized by fusion transcripts of the RELA gene and consequent pathological activation of the NFkB pathway. These tumors represent the majority of supratentorial ependymomas in children. The validation of diagnostic tools to identify this clinically relevant ependymoma entity is essential. Here, we have used interphase fluorescent in situ hybridization (FISH) for C11orf95 and RELA, immunohistochemistry (IHC) for p65‐RelA and the recently developed DNA methylation‐based classification besides conventional histopathology, and compared the precision of the methods in 40 supratentorial pediatric brain tumors diagnosed as ependymomas in the past years. Reverse transcription PCR (RT‐PCR) and RNA sequencing were performed to explore discordant cases. Furthermore, we integrated imaging and clinical features as additional layers of information. The concordance between nuclear RelA expression by IHC and RELA FISH was 100%. Concordance between IHC and DNA methylation profiling, and between FISH and DNA methylation profiling was also high (96.4% and 95.2%, respectively). Thirty‐four out of 40 (85%) cases were confirmed by integrated diagnoses as ependymal tumors, including 22 RELA ‐fused ependymomas (71% of ependymal tumors), two YAP1‐ fused ependymomas (6%), six non‐ RELA /non‐ YAP1 ependymomas (18%) and four ependymal/subependymal mixed tumors (12%). Ependymal/subependymal mixed tumors had an excellent clinical outcome despite the presence of histopathological signs of malignancy, suggesting that these tumors should not be diagnosed as classic ependymomas. DNA methylation profiling helped in the differential diagnosis of RELA‐ fused ependymomas. IHC and FISH, which are available in the majority of pathology laboratories, are valuable tools to identify RELA ‐fused ependymomas.